PENGARUH TINGKAT PERPUTARAN KAS, PERPUTARAN PIUTANG, LIKUIDITAS, DAN PERTUMBUHAN KOPERASI PADA RENTABILITAS EKONOMI - Teja Hadinata, Ngakan Putu; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2016)
Cooperative serves as an economic institution for profit, for the welfare of members in particular, as well as the surrounding community at large. The role and benefits of cooperatives in Indonesia is very important, because the cooperative opened the gate Small and Medium Enterprises (SMEs), creating an independent community, driving the economy to create new jobs. The study was conducted at the Cooperative Market Srinadi Klungkung Year 2012-2014. Samples were financial statements of each business unit in Cooperative Market Srinadi Klungkung a total of 11 business units in the year 2012-2014 were selected by nonprobability sampling method. The collection of data in the form of documentation. The analysis technique used is multiple linear regression. Based on the results of analysis show that the level of cash turnover and accounts receivable turnover significant positive effect on economic profitability, while liquidity levels and growth of cooperatives does not significantly influence economic profitability.
Keywords: Turnover Rate Cash, Accounts Receivable Turnover, Liquidity, Cooperative Growth, Profitability Economy